KOMPETENSI PEKERJA SOSIAL DALAM PELAKSANAAN TUGAS RESPON KASUS ANAK BERHADAPAN DENGAN HUKUM DI CIANJUR - Ellya Susilowati (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2017)
AbstractThis research aims to assess the competence of Social Workers as a profession mandated by Law Number 11 of 2012 on the criminal justice system children in the handling of children in conflict with the law (ABH), especially in performing the case response task to ABH. This research used qualitative descriptive method to seven people who carry out the task of ABH cases response in Cianjur Regency. Data collection techniques used were interviews, observation and documentation study. The results showed that the Social Worker in Cianjur has implemented ABH case response. The implementation of the ABH cases response under the control of Cianjur Regency social service with the support of the child and family support centre of Save the Children. Implementation of the cases response has not referring to the response stage such cases the guidelines of the Directorate of Social Rehabilitation for Children, in which case the response must perform duty service: 1) the emergency; 2) crisis intervention; 3) assisting the completion of the case; 4) social rehabilitation; and 5) the strengthening of child and family services. However, some Social Workers carry out the case response based on the stage of social work and case management approach. The competence of social workers are already using a framework of knowledge, skills and values of social work especially the practice of social work with children.the  recommendations from this research are to: 1) The Directorate of Child Social Rehabilitation Ministry of Social Affairs to continue to disseminate ABH case response and technical assistance for ABH cases response; 2) the child's social worker conduct periodic discussion and sharing about the competence with regard to the response of social work cases ABH.   Keywords: Case Response, Children in Conflict with The Law, Social WorkerAbstrakPenelitian ini dilakukan untuk mengkaji kompetensi Pekerja Sosial sebagai profesi yang dimandatkan Undang-Undang Nomor 11 Tahun 2012  tentang Sistem Peradilan Pidana Anak dalam penanganan Anak Berhadapan dengan Hukum (ABH), khususnya dalam melaksanakan  tugas respon kasus kepada ABH.  Penelitian ini menggunakan metode kualitatif dengan metode deskriptif kepada tujuh orang Pekerja Sosial yang melaksanakan tugas respon kasus ABH di Kabupaten Cianjur. Teknik Pengumpulan data yang digunakan adalah wawancara, observasi, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa Pekerja Sosial di Kabupaten Cianjur telah melaksanakan respon kasus ABH. Pelaksanaan respon kasus ABH ini dibawah kendali Dinas Sosial Kabupaten Cianjur dengan dukungan dari Pusat Dukungan Anak dan Keluarga Save The Children. Pelaksanaan respon kasus belum merujuk pada tahapan respon kasus seperti pedoman dari Direktorat Rehabilitasi Sosial Anak, dimana dalam melakukan respon kasus harus melaksanakan tugas layanan: 1)  kedaruratan; 2)  intervensi krisis; 3) pendampingan penyelesaian kasus; 4) rehabilitasi sosial; dan 5)  layanan penguatan anak dan keluarga. Namun demikian, beberapa Pekerja Sosial melaksanakan respon kasus berdasarkan tahapan pekerjaan sosial dan pendekatan manajemen kasus. Kompetensi pekerja sosial sudah menggunakan kerangka pengetahuan, keterampilan dan nilai dari pekerjaan sosial khususnya praktik pekerjaan sosial dengan anak. Rekomendasi dari penelitian ini adalah kepada: 1) Direktorat Rahebilitasi Sosial Anak Kementerian Sosial untuk terus melakukan sosialisasi respon kasus ABH dan bimbingan teknis untuk respon kasus ABH; 2) Pekerja sosial anak melakukan diskusi dan sharing berkala tentang kompetensi pekerjaan sosial berkaitan dengan respon kasus ABH. Kata kunci:  ABH, Pekerja Sosial, Respon Kasus